PENGGUNAAN FILM BERBAHASA INGGRIS DENGAN ENGLISH SUBTITLE DALAM MENINGKATKAN KETERAMPILAN LISTENING - Dodi Mulyadi; Yulia Mutmainnah (Universitas Muhammadiyah Semarang, 2015)
Listening skill is the first skill learned in learning language. The research will use English movie by English subtitle. Watching English movie by English subtitle can be the one of alternative way in teaching Listening comprehension. Akeelah and the Bee is the movie that will be used by researcher to facilitate and motivate students in learning English of listening skills enthusiastically without any burden. The study was conducted using classroom action research in undergraduate program of English Education Department at Semarang Muhammadiyah University in the academic year 2014/2015. The data was collected from a questionnaire, observation note of performance, pre-test and posttest. The study was conducted with cycle model through the steps of planning, conducting, observation, and reflection. The results of this study show a significant relationship between students' learning by English movie with subtitle related to their listening skills as shown in their improvement of post test and positive responses of students. The questionnaire shows that more than 75% students felt easy to understand listening materials from native speakers. Consequently, it was suggested that teaching learning process using English movie with English subtitle is recommended into learning process to improve students' listening skills in English language classroom.Keywords: English movie, English subtitle and listening skill